Mens - Vuur - Aarde. - De Vogelaere, Fons; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1986)
Bervoets, Fred ; Coorevits, Raf ; De Bruyne, Dees ; De Vogelaere, Fons ; D'Haese, Lebuïn ; D'Haese, Roeland Pietersz ; Dionyse, Carmen ; Ghysels, Marc ; Goossens, Walter ; Pauwels, Achiel ; Van de Perre, Harold ; Vandercam, Serge ; Van Gysegem, Paul ; Vermeersch, José ; Vervisch, Godfried
Mens - Vuur - Aarde, Hof ter Nederloo, Sint-Pieters-Leeuw, 28 november 1986 - 4 janauri 1987
boek